2020
DOI: 10.1007/s43465-020-00281-6
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Femoral Shaft Fracture: An Age-Based Treatment Algorithm

Abstract: Purpose Fractures of the femoral shaft in children are common. The rates of bone growth and remodeling in children vary according to their ages, which affect their respective management. Methods This paper evaluates the incidence and patterns of pediatric femoral shaft fracture and the current concepts of treatments available. ResultsThe type of fracture-closed or open; stable or unstable-needs to be taken into account. Child abuse should be suspected in fractures sustained by infants. For younger children, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…Several interventions have been reported for the treatment of length-unstable femoral shaft fracture in children, including traction, followed by spica casting, ESIN, plating, rigid nailing, and external fixator with various constructs ( 15 ). Spica casting following traction requires prolonged hospital stay and demonstrates limited ability of restoring the limb length.…”
Section: Discussionmentioning
confidence: 99%
“…Several interventions have been reported for the treatment of length-unstable femoral shaft fracture in children, including traction, followed by spica casting, ESIN, plating, rigid nailing, and external fixator with various constructs ( 15 ). Spica casting following traction requires prolonged hospital stay and demonstrates limited ability of restoring the limb length.…”
Section: Discussionmentioning
confidence: 99%
“…Femoral shaft fractures are the most common pediatric lower extremity fracture and the leading cause among pediatric orthopedic injuries that require hospitalization [1,2]. The incidence of pediatric femoral shaft fractures in the United States is estimated to be 20 per 100,000 children per year [1,[3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of injury leading to a femoral shaft fracture vary based on the patient's age. Falls are the most common mechanism for children under the age of six, while high-impact sports, motor vehicle-pedestrian accidents, and motor vehicle accidents are more common among preadolescents and adolescents [1][2][3]. Hunter et al found that black males between the ages of 14 and 17 years were at the highest risk for femoral shaft fractures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The femoral shaft fractures treatment varies according to the size and age of the children, the associated injuries and local practice (Prajapati et al, 2019;Mehmood et al, 2019). Contemporary methods of treating femoral shaft fractures comprise many forms of traction, prompt and delayed spica casting, lexible nailing, plate ixation, external ixation and traditional intramedullary nailing for adolescents and older children (Liau et al, 2020;Saeed, 2019). The use of surgical methods is limited by complications such as infections and joint injuries.…”
Section: Introductionmentioning
confidence: 99%